A Critiquing of Masculinity Leadership Syndrome in African Organizations: A Lens From Kitchen to the Palace of Modern Organizations (Global Journal of Management and Business Research, 2020)
Scholars have described leadership based on different experiences and practices. It is a process whereby an individual influences a group of individuals to achieve a common goal. This paper is an examination and critiquing of the masculinity leadership syndrome in African organizations. It is common traditions, which Africa and Africans perceived leadership as mainly the affairs of the men folks in which the women are alienated from organizational decisionmaking; hence the delineation of the roles of women in the Kitchen while the men have to sit at the palaces to make decisions on rulership and governance and that man is chosen divinely by nature to lead and govern his environment. This they strongly believed in the "Great Man Leadership Theory" which was popularized by Carlyle, Thomas, 1940. Africans generally believed that leadership is an exclusive reserve of the great men and not great women.
Keywords: leadership; biases; organizations; power; in clusion